Effect of spironolactone wash-out on albuminuria after long-term treatment in individuals with type 2 diabetes and high risk of kidney disease-An observational follow-up of the PRIORITY study - Wasehuus, Victor; Rotbain Curovic, Viktor; Tofte, Nete; Lindhardt, Morten; Currie, Gemma; Delles, Christian; Frimodt-Møller, Marie; Mischak, Harald; von der Leyen, Heiko; Hansen, Tine Willum; Kümler, Thomas; Persson, Frederik; et al. (Wiley, 2025)
This study aimed to explore the effect of discontinuation of long-term spironolactone treatment on markers of kidney function in individuals with type 2 diabetes (T2D) at high risk of kidney disease enrolled in the Proteomic prediction and Renin angiotensin aldosterone system Inhibition prevention Of early diabetic nephRopathy In TYpe 2 diabetic patients with normoalbuminuria (PRIORITY) study.